Beyond Ethnic Tidbits: Toward a Critical and Dialogical Model in Multicultural Social Justice Teacher Preparation - Convertino, Christina (International Journal of Multicultural Education, 2016)
This praxis article outlines the value of using a critical and dialogical model (CDM) to teach multicultural social justice education to pre-service teachers. Based on practitioner research, the article draws on the author’s own teaching experiences to highlight how key features of CDM can be used to help pre-service teachers move beyond thinking about multicultural education as ethnic tidbits. Illustrative examples of CDM-in-use demonstrate that learning about multicultural social justice education is a social and developmental process that requires teacher educators to scaffold complex ideas by using dialogical approaches to learning that incrementally build on emergent and shared knowledge.